Pengaruh E-Service Quality dan Kepercayaan Terhadap Keputusan Pembelian Studi Pada Pelanggan Marketplace Aplikasi Blibli di Kota Bandung - Andi Setiawan; Mochammad Mukti Ali (eCo-Fin, 2025)
The e-commerce fields is encounter very grow fast, driven by increasing internet penetration and the use of mobile devices among the public. In Indonesia, various e-commerce platforms compete to attract consumer attention, including Blibli. Blibli is a marketplace platform owned by PT Global Digital Niaga Tbk, which operates under the trade name Blibli Tiket Group. This review aims to examine the impact of e-service quality and confidence in purchasing decisions, focusing on users of the Blibli marketplace application in Bandung City. The study adopts a quantitative approach, utilizing both descriptive and verification methods. The study population consists of Blibli app users, selected based on the average number of active users, with a sample size of 100 respondents. Data analysis includes tests for data quality, classical assumptions, and the relationship between variables. Hypothesis testing is conducted using the t-test (partial) and F-test (simultaneous). All data processing is carried out using SPSS version 26. The regression analysis reveals that e-service quality (6.864) and trust (4.831) significantly influence purchasing decisions, with an F-value of 59.548 and a p-value of 0.000. These findings indicate that both e-service quality and trust have a strong and positive effect on purchasing decisions.